Criteria for the administration of systemic antimicotic therapy in surgical intensive care units (literature review) - B. Z. Belotserkovskiy; E. B. Gelfand; A. O. Bykov; O. A. Mamontova; D. N. Protsenko (Тазовая хирургия и онкология, 2019)
This review focuses on the practical aspects of prevention and treatment of fungal infections in surgical patients. It covers epidemiology and risk factors for invasive candidiasis, updates on the etiological structure of fungal infections in patients in critical conditions, and provides the information on drug sensitivity of Candida species. The authors discuss the limitations of cultural and non-cultural diagnostic methods used in invasive candidiasis, emphasizing the importance of analyzing the existing risk factors in combination with a comprehensive assessment of clinical and laboratory data for timely initiation of adequate antifungal therapy. The review provides a brief description of currently available antimicotics, including polyenes, triazoles, and echinocandins. It also describes the benefits of anidulafungin, which does not interact with other drugs and has no negative effect on the liver and kidney. The article also covers indications for antifungal agents in surgical intensive care units in accordance with international and Russian guidelines. A cohort of patients with abdominal diseases requiring preventive and empirical treatment with antimicotics is described. In additions to that, the manuscript contains a rationale for the use of echinocandins in targeted therapy of invasive candidiasis.